A qualitative study of stigma in patients with low anterior resection syndrome of rectal cancer (直肠癌低位前切除综合征患者病耻感的质性研究) - WEN Ruizhen (温瑞珍); CHEN Piao (陈飘); LI Yalan (李亚兰); CAO Aifang (曹爱芳); WANG Miaolan (王淼兰); ZHENG XiaoXuan (郑筱暄); PENG Hui (彭慧) (中西医结合护理)
Objective To investigate the real experience, influencing factors and coping method of stigma in patients with low anterior resection syndrome(LARS) of rectal cancer, and to provide reference for medical staff to formulate targeted intervention measures. Methods Purposive sampling method was used to select the patients with LARS symptoms after rectal surgery of a Class Ⅲ Grade A hospital in Guangzhou from March 2024 to May 2024 as subjects. The descriptive qualitative study was used to conduct face-to-face semi-constructive interviews with patients, and the recording materials were processed by Nvivo12. 0 software. Results The stigma of patients with LARS can be summarized into three themes. Theme 1: Stigma experiences, including feelings of shame, discrimination, and loneliness; Theme 2: Determinants of stigma, including disease factors and lack of public knowledge; Theme 3: Stigma sensing approaches, including avoiding social contact, concealing the condition, and actively coping. Conclusion Patients with LARS of rectal cancer have strong stigma. Medical staff should pay full attention to the stigma of patients and provide them with relevant nursing intervention and psychological support. (目的 深入了解直肠癌低位前切除综合征(LARS)患者病耻感的真实体验、影响因素和应对方式, 为医护人员制订针对性的干预措施提供参考依据。方法 采用目的抽样法, 选取2024年3月—5月医院肛肠外科直肠癌保肛术后出现LARS的患者作为研究对象。采用质性研究中的现象学研究方法对患者进行深度访谈, 采用Colaizzi七步分析法分析资料并提炼主题。结果 LARS患者的病耻感可归纳为3个主题, 分别是: ①病耻感体验: 羞耻感、受歧视感、孤独感; ②病耻感影响因素: 疾病因素、文化因素、公众知识缺乏; ③病耻感应对方式: 主动社交回避、不当的自我管理、刻意隐瞒病情、积极应对。结论 直肠癌LARS患者存在较强的病耻感, 医护人员需充分关注并提供相关的护理干预和心理支持。)